EFFECT OF AGE AND SEASON ON PRODUCTION PERFORMANCE AND EGG QUALITY OF LAYING HENS FROM DIFFERENT REARING SYSTEMS - Rakonjac Simeon; Petrovi D. Milun; Bogosavljevi-Boakovi Sne~an; a`krbi Zdenk; a Peri Lidija; Doskovi Vladimir; Petrievi Vesneli (Journal of Animal and Plant Sciences, 2018)
The aim of this study was to evaluate the effect of hen's age and season on production performance and egg quality of laying hens from three different rearing systems. The tested rearing systems were: cage, floor and organic (30 birds Isa Brown hybrid per group). Experimental period was divided into four sub-periods (4 seasons per 13 weeks) and weekly were recorded: deposition, daily produced egg mass, feed consumption, feed conversion in egg mass and mortality. Eggs were collected for analyses during the all four seasons, in all the different phases of the productive activity (summer - 24 weeks hen's age, autumn - 40 weeks hen's age, winter - 56 weeks hen's age and spring - 64 weeks hen's age). In these samples (fifteen eggs per group, eggs were one day old) were evaluated external and internal egg quality parameters: egg weight, egg shape index, albumen share, yolk share, shell share, albumen height, Haugh unit and yolk colour. Age and season, as well as the rearing system, have a significant effect on the production results and egg quality of laying hens. Generally, in summer and autumn, the most of production performances were the best in cage rearing system, while organic system was superior in spring. Egg weight and yolks share were increased, while egg shape index, albumen share, albumen height and Haugh unit were decreased with hen's age. Generally, eggs from cages and the floor had a greater weight compared to organic. Organic eggs had higher albumen height and Haugh unit score in the spring compared to the cage and floor eggs. Yolk colour of the floor and cage eggs most dependent on the hen's age, on the other hand - yolk colour of organic hens most dependent on the grass availability at the outlet.
Keywords: Laying hens; egg quality; production; rearing systems; season.